Signifying Europe - Fornäs, Johan (Intellect, 2012)
Signifying Europe provides a systematic overview of the wide range of symbols used to represent Europe and Europeanness, both by the political elite and the broader public. Through a critical interpretation of the meanings of the various symbols-and their often contradictory or ambiguous dimensions-Johan Fornäs uncovers illuminating insights into how Europe currently identifies itself and is identified by others outside its borders. While the focus is on the European Union's symbols, those symbols are also interpreted in relation to other symbols of Europe. Offering insight into the cultural dimensions of European unification, this volume will appeal to students, scholars and politicians interested in European policy issues, cultural studies and postnational cultural identity.